Relapsing Polychondritis in a Patient with Ankylosing Spondylitis Using Etanercept - Azevedo, Valderilio Feijó (Hindawi Publishing Corporation, 2014)
Relapsing polychondritis (RP) is an autoimmune disease characterized by recurrent episodes of inflammation and progressive destruction of cartilaginous tissues, especially of the ears, nose, joints, and tracheobronchial tree. Its etiology is not well understood, but some studies have linked its pathophysiology with autoimmune disease and autoantibody production. We described a case of a 46-year-old male patient with ankylosing spondylitis who developed RP after the use of etanercept. Few similar cases have been described in the literature. However, they show a possible association between the use of biological inhibitors of tumor necrosis factor (anti-TNFα), which potentially produces autoantibodies, and the development of RP. The treatment was based on data in the literature and included the cessation of biological therapy and the addition of corticosteroids with substantial improvement.